Friction Coefficient and Wear Rate of Copper Mating with Smooth and Rough Stainless Steel 304 Counterfaces - Chowdhury, Mohammad Asaduzzaman; Nuruzzaman, D. M.; Roy, Biplov Kumar; Rahman, Muhammad Mahmudur; Azad, Md. Abul Kalam; Rahman, Md.Mijanur; Bhumik, Shazib (americanscience.org, 2013)
In the present study, friction coefficient and wear rate of copper sliding against SS 304 are investigated experimentally. In order to do so, a pin on disc apparatus is designed and fabricated. Experiments are carried out when smooth or rough SS 304 pin slides on copper disc. Experiments are conducted at normal load 10, 15 and 20 N, sliding velocity 1, 1.5 and 2 m/s and relative humidity 70%. Variations of friction coefficient with the duration of rubbing at different normal loads and sliding velocities are investigated. Results show that friction coefficient is influenced by duration of rubbing, normal load and sliding velocity. In general, friction coefficient increases for a certain duration of rubbing and after that it remains constant for the rest of the experimental time. The obtained results reveal that friction coefficient decreases with the increase in normal load and sliding velocity for copper mating with smooth or rough SS 304 counterface. Moreover, wear rate increases with the increase in normal load and sliding velocity. The magnitudes of friction coefficient and wear rate are different depending on sliding velocity and normal load for both smooth and rough counterface pin materials.